Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase

Altered Octopamine synthesis impairs tyrosine metabolism affecting Helicoverpa armigera vitality - Patil, Yogita P.; Wagh, Deepti S.; Barvkar, Vitthal T.; Gawari, Shyam K.; Pisalwar, Priyanka D.; Ahmed, Shadab; Joshi, Rakesh S. (Pesticide Biochemistry and Physiology, 2025)
Tyramine (1-hydroxylase (T(1H) is a key enzyme in the biosynthesis of octopamine (OA), a vital neurohormone in invertebrates. This study explores the expression patterns and functional role of Helicoverpa armigera T(1H (HaT(1H) across various tissues and developmental stages. HaT(1H expression was highest in the head and adult male stages, reflecting tissue-specific and developmental regulation. HaT(1H silencing significantly increased locomotion and decreased feeding behavior. OA supplementation in silenced insects or HaT(1H overexpression showed a contrary effect on locomotory and feeding behavior. In silico screening and inhibitory assays identified tomatidine, a tomato-derived metabolite, as a potent HaT beta H inhibitor with strong binding affinity. In vivo bioassays confirmed tomatidine's inhibitory effects, reducing feeding and increasing mortality in H. armigera. Modulation in HaT(1H expression or activity disturbs the tyrosine metabolic pathway, with altered levels of tyramine, octopamine, and dopamine. These results highlight HaT(1H as a key regulator of OA biosynthesis, influencing insect feeding, locomotion, and overall survival. The present study also introduces tomatidine as a potential candidate for insect control, given its ability to disrupt HaT beta H function. This work provides new insights into the physiological roles of HaT beta H and offers promising avenues for developing targeted pest management strategies.
Keywords: Helicoverpa armigera; Octopamine biosynthesis; Tomatidine; Tyramine (1-hydroxylase (HaT(1H); Tyrosine metabolic pathway